2003
DOI: 10.1128/jcm.41.2.586-591.2003
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Diversity among Streptogramin A-Resistant Staphylococcus aureus Isolates Collected in French Hospitals

Abstract: We analyzed 62 clinical isolates of streptogramin A-resistant (SGA r ) Staphylococcus aureus collected between 1981 and 2001 in 14 hospitals located in seven French cities. These isolates, including five with decreased susceptibility to glycopeptides, were distributed into 45 antibiotypes and 38 SmaI genotypes. Each of these genotypes included between 1 and 11 isolates, the SmaI patterns of which differed by no more than three bands. Although numerous clones were identified, we observed the spread of monoclona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…This phenotype is similar to that conferred by the lsa gene in Enterococcus faecalis, although the levels of resistance to lincosamides were much lower for staphylococci with the vga(A) and the vga(A)v genes (38). We suggest, therefore, that vga(A) or its variant, vga(A)v, is involved in the LSA phenotype occasionally found among staphylococcal isolates (14,17,24).…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…This phenotype is similar to that conferred by the lsa gene in Enterococcus faecalis, although the levels of resistance to lincosamides were much lower for staphylococci with the vga(A) and the vga(A)v genes (38). We suggest, therefore, that vga(A) or its variant, vga(A)v, is involved in the LSA phenotype occasionally found among staphylococcal isolates (14,17,24).…”
Section: Resultsmentioning
confidence: 69%
“…To the best of our knowledge, this has never been described. The detection of this gene in clinical strains might therefore be of importance for prediction of the in vivo activity of quinupristin-dalfopristin (2,11,17,24).…”
Section: Resultsmentioning
confidence: 99%
“…and has never been found in gram-negative bacteria. In S. aureus strain BM12235, carrying the major facilitator streptogramin efflux gene vga(B) and the streptogramin acetyltransferase gene vat(B), it was possible to identify also the presence of vga(A)v, an ATP-binding transporter gene which is commonly associated with vga(B) and vat(B) (11,12). DNA sequence analysis showed that vga(A)v of BM12235 was essentially identical (99% identity at the DNA level) to vga(A)v of S. aureus BM3327 (GenBank accession no.…”
Section: Resultsmentioning
confidence: 99%
“…There is little prospect of eradicating staphylococcal disease in the short term so effective antibiotics are of great importance. Fortunately, both linezolid and Synercid (a streptogramin A/B combination) are newly licensed for use against staphylococci but resistance to streptogramins is already present among hospital staphylococci and its prevalence can be expected to increase with the widespread use of Synercid (Haroche et al, 2003).…”
Section: Staphylococcus Special Issuementioning
confidence: 99%